2006
DOI: 10.1038/sj.ijo.0803404
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health and psychosocial outcomes from surgically induced weight loss: results obtained in patients not attending protocolled follow-up visits

Abstract: Objective: Obesity management is focused at weight loss to obtain health, psychological and social benefits. Outcomes from controlled trials, however, do not reflect the everyday routine practice. Therefore, we aimed to investigate the results from surgically induced weight loss in patients devoid of a protocol-wise follow-up, who were visited at home. Patients and methods: Patients who underwent a vertical banded gastroplasty or a gastric bypass between 1980 and 1997 were eligible. Body weight and height were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
0
30
2
Order By: Relevance
“…Overall, we found statistically significant improvements in all quality of life measures at 24 months. Others have also noted statistically significant and clinically relevant improvements in healthrelated quality of life measures after surgically induced weight loss [24,[73][74][75][76]. However, few have assessed the relationship between weight loss, subjective sleepiness, and health-related quality of life [24].…”
Section: Discussionmentioning
confidence: 92%
“…Overall, we found statistically significant improvements in all quality of life measures at 24 months. Others have also noted statistically significant and clinically relevant improvements in healthrelated quality of life measures after surgically induced weight loss [24,[73][74][75][76]. However, few have assessed the relationship between weight loss, subjective sleepiness, and health-related quality of life [24].…”
Section: Discussionmentioning
confidence: 92%
“…For data collection and analyses, specific categories were determined and a spreadsheet created in order to record observations. Categories were generated based on the current research questions as well as previous research and best-practice recommendations; for instance, research shows that regular follow-up and attendance at support groups are associated with improved outcomes [23][24][25]. Categories included psychological assessment, pre-and post-surgical behavioral requirements, support groups, follow-up protocol, and staffing.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Of the 14 studies analyzing the association between personality disorders and postoperative weight loss (n=3,360 patients), 7 reported a negative association [27,49,51,62,103,131,132], 3 reported no association [54,109,133], and 4 reported a positive association [48,52,134,135]. Tsushima et al [62] reported that patients with ≥50% EWL compared to those with <50% EWL at 12 months had a significantly lower incidence of personality disorder subscales including phobia and paranoia, using the MMPI-2 [119].…”
Section: Other Psychiatric Disordersmentioning
confidence: 96%
“…Mathus-Vliegen et al used The Dutch Eating Behaviour Questionnaire [113], which assesses eating behaviors such as emotional eating and conscious restriction of intake, and reported a significant inverse relationship between weight change and emotional eating scores [109]. Gentry et al used the Eating Behavior Questionnaires II (series of open-ended questions about patient's history of obesity) and III (structured interview regarding food and activity patterns) and found that patients who ate in response to stress lost less weight after surgery compared to patients who ate in response to pleasant feelings or a sense of accomplishment (P<0.005) [110].…”
Section: Other Maladaptive Eating Habitsmentioning
confidence: 99%
See 1 more Smart Citation